Microbubbles size distribution at different palm oil mill effluent (POME) temperatures for oil recovery study / Nurul Hazwani Mohamad ... [et al.] - Mohamad, Nurul Hazwani; Sulaiman, Alawi; Mokhtar, Mohd Noriznan; Samsu Baharuddin, Azhari (Research Management Institute (RMI), 2017)
Palm Oil Mill Effluent (POME) is the largest contributor of biomass from the palm oil milling industry. Conventional method of POME treatment using ponding system should be improved because of huge land resource requirement. In this study, microbubbles technology was applied to understand the recovery rate of residual oil from POME at different operating temperatures. Temperature for POME wasset at 27 o C, 30 o C and 50 o C to determine the microbubble size distributions and characteristics at different POME temperature. At each temperature, the size of microbubbles was measured based on six size range; <10 μm, (11-20) μm, (21-30) μm, (31-40) μm, (41-50) μm and >50 μm. The results showed that at different temperatures, the microbubbles size distribution varies and the smallest group of microbubbles(<10μm) was generated at 50o C. According to StokeEinstein equation, at higher temperature, smaller size of microbubbles is generated because of the gas diffusion factor into liquid.